Using Kanban to Improve Indonesian Health Coverage Patient Task Id at Astrini Hospital Wonogiri - Permanajati, Agung; Putri Maya Puspita (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Hospital is a complex industry organization comprises providers, therapies, physical location, technology and innovation. Digital transformation from Indonesian Health Coverage making us to give their patient excellence health service. For maintain our team to give patient best quality service excellence, we aplicated one of tool lean management such as kanban Purpose: to see either kanban is effective way to evaluate and improve our quality service delivery Method: We made kanban board from discussion within our team include, director, head divison, manager and staff. After we settle it, we choose which item in backlog going to in progress for first week until foruth week. we done it one by one and if there blocked that we can’t achive about the item in backlog collum we will move it to blocked colloumn. Result: As lean management philosophy, we must correct our process and eliminate waste. Under supervising. from 30 October - 6 november 2023 our score just 38 -39%. after 4 weeks use kanban, our score imprvoe to above 90%. We make change in our workflow and it’s an effective way. Conclusion: Kanban with kanban board is one of many tool in lean management to improve our product. They can be done in healthcare industry. Lean is recognised as a systematic approach, it will improve about efficiency and effectivity by eliminating waste and pursuing perfection with minimal resources.